Hydrologic Controls on Nitrogen and Phosphorous Dynamics in Relict Oxbow Wetlands Adjacent to an Urban Restored Stream1. (9th May 2014) - Harrison, Melanie D.; Miller, Andrew J.; Groffman, Peter M.; Mayer, Paul M.; Kaushal, Sujay S.
Abstract Although wetlands are known to be sinks for nitrogen (N) and phosphorus (P), their function in urban watersheds remains unclear. We analyzed water and nitrate (NO3−) and phosphate (PO43−) dynamics during precipitation events in two oxbow wetlands that were created during geomorphic stream restoration in Baltimore County, Maryland that varied in the nature and extent of connectivity to the adjacent stream. Oxbow 1 (Ox1) received 1.6‐4.2% and Oxbow 2 (Ox2) received 4.2‐7.4% of cumulative streamflow during storm events from subsurface seepage (Ox1) and surface flow (Ox2). The retention time of incoming stormwater ranged from 0.2 to 6.7 days in Ox1 and 1.8 to 4.3 days in Ox2. Retention rates in the wetlands ranged from 0.25 to 2.74 g N/m2/day in Ox1 and 0.29 to 1.94 g N/m2/day in Ox2. Percent retention of the NO3−‐N load that entered the wetlands during the storm events ranged from 64 to 87% and 23 to 26%, in Ox1 and Ox2, respectively. During all four storm events, Ox1 and Ox2 were a small net source of dissolved PO43− to the adjacent stream (i.e., more P exited than entered the wetland), releasing P at a rate of 0.23‐20.83 mg P/m2/day and 3.43‐24.84 mg P/m2/day, respectively. N and P removal efficiency of the oxbows were regulated by hydrologic connectivity, hydraulic loading, and retention time. Incidental oxbow wetlands have potential to receive urban stream and storm flow and to be significant N sinks, but they may be sources of P in urban watersheds.